Stan badań nad dziejami Towarzystwa do Ksiąg Elementarnych - Taylor-Jaskólska, Sarah (Biuletyn Historii Wychowania, 2026)
The article explores the state of research on the Society for Elementary Books, a key educational institution in 18th-century Poland established in 1775 to support the reforms of the National Education Commission. The Society’s mission was to develop a modern curriculum aligned with Enlightenment ideals and tailored to national needs. This literature review highlights significant studies, particularly those by Janina Lubieniecka, who analyzed some of the the textbooks and educational programs created by the Society. Although many sources were lost during wars, the surviving studies continue to offer rich insights into the Society’s role in shaping Poland’s educational system.